2009
DOI: 10.1002/jso.21352
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological features of remnant gastric cancers, after gastrectomy for synchronous multiple gastric cancers

Abstract: Patients with synchronous multiple gastric cancers are more susceptible to the development of secondary cancers in their remnant stomach. These patients need careful follow-up after initial gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…We speculate that this is because the duodenogastric reflux after Billroth II anastomosis induces the primary gastric remnant cancer in the long term after benign gastric ulcer surgery, but does not induce secondary metachronous cancer in the gastric remnant after early gastric cancer surgery [33]. Fujita et al [11] have reported that the gastric remnant after synchronous multiple cancer surgery has a higher risk of metachronous cancer. They also have reported that a combination of diffuse-type synchronous multiple cancers at the time of the initial surgery was a potential risk factor for metachronous cancer in the gastric remnant [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that this is because the duodenogastric reflux after Billroth II anastomosis induces the primary gastric remnant cancer in the long term after benign gastric ulcer surgery, but does not induce secondary metachronous cancer in the gastric remnant after early gastric cancer surgery [33]. Fujita et al [11] have reported that the gastric remnant after synchronous multiple cancer surgery has a higher risk of metachronous cancer. They also have reported that a combination of diffuse-type synchronous multiple cancers at the time of the initial surgery was a potential risk factor for metachronous cancer in the gastric remnant [34].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of synchronous multiple gastric cancers has been reported to occur in 5-8 % of surgically resected stomachs [7][8][9][10][11]. However, a comprehensive evaluation using serial sections of the whole stomach revealed that it was 13-15 % [10,12], which suggests a higher incidence of latent lesions in the whole stomach [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, multiple gastric cancers tend to be more susceptible to the development of metachronous lesions than solitary gastric cancers. 16 After ESD, 6.2% to 14% of patients subsequently developed metachronous cancer. 17,18 However, most metachronous lesions were intramucosal tumors with no lymphovascular involvement and no LN metastases, indicating the potential for additional ESD or other local therapy instead of gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Signs of advanced disease-multiple liver metastases, extensive peritoneal carcinomatosis, enlarged perigastric lymph nodes and pancreatic involvement were not found. anism responsible for the coexistence of these tumors is not clear, special carcinogens, H. pylori infection and genetic mutations have been considered agents capable of inducing the transformation of different cell lines from the gastrointestinal tract [2][3][4] . Family history, genetic factors, immunologic mechanisms, chemotherapy, and radiation therapy all likely contribute to the development of multiple carcinomas [5,6] .…”
Section: Discussionmentioning
confidence: 99%